ENT600: Parent learning management system / Azlindahani Othman … [et al.] - Othman, Azlindahani; Rapie, Nurul 'Ain; Zul, Maisarah; Musa, Syamimi; Abdussalam, Siti Nurul Hidayu (2018)
Research shows that high-quality preschool programs not only improve school readiness, but also lead to an array of positive academic and life outcomes. State and national leaders have turned their attention to expanding preschool enrolment as one strategy for improving student success. Yet while preschool enrolment has risen consistently in recent years, enrolment alone is not enough. We must also ensure that early childhood programs offer high quality, developmentally appropriate instruction that is aligned with Malaysian education standards that meets the full range of young children's developmental needs. Early childhood offers educators a unique set of opportunities and challenges. Young children undergo remarkable growth in cognitive, physical, social, and emotional development. However, preparing young children for future success is not simply a matter of introducing challenging academic work to early childhood classrooms. Instruction, as well as assessment, must take into consideration the special challenges of early childhood. Our youngest learners benefit most when "rich literacy and numeracy instruction are combined with music, art, physical, and health education, with time to play and grow socially and emotionally. Their future success is built on this comprehensive foundation. High-quality preschool makes a difference for students and society. For college and career readiness, the education our youngest students receive must be consistent with and connected to early elementary school, address the full range of all students' developmental needs, and work to prepare the whole child for future success as healthy, productive, engaged citizens. The study found parents to be knowledgeable about child development. Most parent indicated all seven domains of child development as important, these domains includes physical, cognitive, language, literacy, social, emotional, and moral development. Parent are the key influencers in their children's lives and play an integral role in their early formative years. Their involvement and the home learning environments they create form an inextricable link to ensuring positive outcomes for children across a range of developments - physical, cognitive, language, moral and socio-emotional. Issues and challenges that parents face and the types of resources that are useful for them in their parenting journey were explored in order to inform the development of their children and link with home learning environment using proper guidance from parent. Thus, reduce parent neglection rate of preschool children.